Analisis Jama’ Taksir Dalam Al-Qur’an Surat Al-Maidah Dan Metode Pembelajarannya - Muslihatul Istiqomah; Nurkholis; Doni Sastrawan (Al Mitsali, 2022)
This research is motivated by the importance of understanding the science of Arabic morphology which is very influential in changing the form of words and their meanings. Jama’ Taksir was chosen because its qiyasi and sima'i nature and has a variety of forms in Surah Al-Maidah and many Arabic learners do not understand that Jama' Taksir has wazan as a measure of word change. The researcher chose Surah Al-Maidah because it contains many Shari'a laws and is one of the long surah. The purpose of this study is to describe the number of Jama' Taksir in Surah Al-Maidah and the process of forming Jama’ Taksir from mufrad to jama’. This research is Literature Research, namely Research that takes research materials from several references or books that are in accordance with the research theme by taking data from the Al-Qur'an surah Al-Maidah using descriptive analysis. The data collection is done by observing the primary and secondary data sources qualitatively. The results of this study, found as many as 72 sentences of Jama’ Taksir contained in 47 verses of the total 120 verses of Surah Al-Maidah. Of the 72 sentences of Jama' Taksir, there are 22 sentence in the form of Jama' Qillah and 50 sentence in the form of Jama' Katsrah. This research is expected to provide benefits and can be used as source in literature research.